Inside Cover: Process Intensification for Cellulosic Biorefineries (ChemSusChem 12/2017). Issue 12 (12th June 2017) - Sadula, Sunitha; Athaley, Abhay; Zheng, Weiqing; Ierapetritou, Marianthi; Saha, Basudeb
Abstract : The Inside Cover picture shows multipurpose use of sugars produced from varieties of advantageous sourced lignocellulosic biomass by an integrated one‐step process. This new energy‐ and water‐efficient process yields up to 95 % theoretical amount of sugars in an inorganic salt solution. The high efficiency and easiness of separation of the products create favorable economics that can enable bio‐based products that are cost‐competitive and sustainable. More details can be found in the Communication by Sadula et al. onpage 2566 in Issue 12, 2017 (DOI:10.1002/cssc.201700183 ).